Kallikrein-8 Proteolytically Processes Human Papillomaviruses in the Extracellular Space To Facilitate Entry into Host Cells - Cerqueira, Carla (J Virol, 2015)
The entry of human papillomaviruses into host cells is a complex process. It involves conformational changes at the cell surface, receptor switching, internalization by a novel endocytic mechanism, uncoating in endosomes, trafficking of a subviral complex to the Golgi complex, and nuclear entry during mitosis. Here, we addressed how the stabilizing contacts in the capsid of human papillomavirus 16 (HPV16) may be reversed to allow uncoating of the viral genome. Using biochemical and cell-biological analyses, we determined that the major capsid protein L1 underwent proteolytic cleavage during entry. In addition to a dispensable cathepsin-mediated proteolysis that occurred likely after removal of capsomers from the subviral complex in endosomes, at least two further proteolytic cleavages of L1 were observed, one of which was independent of the low-pH environment of endosomes. This cleavage occurred extracellularly. Further analysis showed that the responsible protease was the secreted trypsin-like serine protease kallikrein-8 (KLK8) involved in epidermal homeostasis and wound healing. Required for infection, the cleavage was facilitated by prior interaction of viral particles with heparan sulfate proteoglycans. KLK8-mediated cleavage was crucial for further conformational changes exposing an important epitope of the minor capsid protein L2. Occurring independently of cyclophilins and of furin that mediate L2 exposure, KLK8-mediated cleavage of L1 likely facilitated access to L2, located in the capsid lumen, and potentially uncoating. Since HPV6 and HPV18 also required KLK8 for entry, we propose that the KLK8-dependent entry step is conserved. IMPORTANCE Our analysis of the proteolytic processing of incoming HPV16, an etiological agent of cervical cancer, demonstrated that the capsid is cleaved extracellularly by a serine protease active during wound healing and that this cleavage was crucial for infection. The cleavage of L1 is one of at least four structural alterations that prime the virus extracellularly for receptor switching, internalization, and possibly uncoating. This step was also important for HPV6 and HPV18, which may suggest that it is conserved among the papillomaviruses. This study advances the understanding of how HPV16 initially infects cells, strengthens the notion that wounding facilitates infection of epidermal tissue, and may help the development of antiviral measures.